The 1, 2, 3-triazole derivative KP-A021 suppresses osteoclast differentiation and function by inhibiting RANKL-mediated MEK-ERK signaling pathway. (December 2015) - Ihn, Hye Jung; Lee, Doohyun; Lee, Taeho; Shin, Hong-In; Bae, Yong Chul; Kim, Sang-Hyun; Park, Eui Kyun
The triazole family of compounds has been implicated in modulating various biological processes such as inflammation, tumorigenesis, and infection. To our knowledge, this is the first study to demonstrate the effects of 1, 2, 3-triazole substituted biarylacrylonitrile compounds, including KP-A021, on the differentiation and function of osteoclasts. KP-A021 and its triazole derivatives, at a concentration that does not cause a cytotoxic response in bone marrow macrophages (BMMs), significantly inhibited osteoclast differentiation induced by receptor activator of nuclear factor-κB ligand (RANKL) and macrophage colony-stimulating factor (M-CSF) as assessed by tartrate-resistant acid phosphatase (TRAP) staining. KP-A021 also dramatically inhibited the expression of marker genes associated with osteoclast differentiation, such as TRAP, cathepsin K ( Cat K ), dendritic cell-specific transmembrane protein ( DC-STAMP ), and nuclear factor of activated T-cells, cytoplasmic 1 ( NFATc1 ). Furthermore, KP-A021 inhibited actin ring formation in osteoclasts as well as resorption pit formation induced by osteoclasts. Analysis of the signaling pathway for KP-A021 indicated that this triazole compound inhibited the RANKL-induced activation of extracellular signal-regulated kinase (ERK) and its upstream signaling molecule, mitogen-activated protein kinase kinase1/2 (MEK1/2). Taken together, these results demonstrate that KP-A021 has an inhibitory effect on the differentiation and function of osteoclasts via modulation of the RANKL-induced activation of the MEK-ERK pathway.